Inhaled anti-TSLP antibody fragment, ecleralimab, blocks responses to allergen in mild asthma. Issue 3 (9th March 2023) - Gauvreau, Gail M.; Hohlfeld, Jens M.; FitzGerald, J. Mark; Boulet, Louis-Philippe; Cockcroft, Donald W.; Davis, Beth E.; Korn, Stephanie; Kornmann, Oliver; Leigh, Richard; Mayers, Irvin; Watz, Henrik; Grant, Sarah S.; et al.
Background: Thymic stromal lymphopoietin (TSLP) is a key upstream regulator driving allergic inflammatory responses. We evaluated the efficacy and safety of ecleralimab, a potent inhaled neutralising antibody fragment against human TSLP, using allergen inhalation challenge (AIC) in subjects with mild atopic asthma. Methods: This was a 12-week, randomised, double-blind, placebo-controlled, parallel-design, multicentre allergen bronchoprovocation study conducted at 10 centres across Canada and Germany. Subjects aged 18–60 years with stable mild atopic asthma were randomised (1:1) to receive 4 mg once-daily inhaled ecleralimab or placebo. Primary end-points were the allergen-induced change in forced expiratory volume in 1 s (FEV1 ) during the late asthmatic response (LAR) measured by area under the curve (AUC3–7h ) and maximum percentage decrease (LAR%) on day 84, and the safety of ecleralimab. Allergen-induced early asthmatic response (EAR), sputum eosinophils and fractional exhaled nitric oxide ( F ENO ) were secondary and exploratory end-points. Results: 28 subjects were randomised to ecleralimab (n=15) or placebo (n=13). On day 84, ecleralimab significantly attenuated LAR AUC3–7h by 64% (p=0.008), LAR% by 48% (p=0.029), and allergen-induced sputum eosinophils by 64% at 7 h (p=0.011) and by 52% at 24 h (p=0.047) post-challenge. Ecleralimab also numerically reduced EAR AUC0–2h (p=0.097) and EAR% (p=0.105). F ENO levels were significantly reduced from baseline throughout the study (p<0.05), except at 24 h post-allergen (day 43 and day 85). Overall, ecleralimab was safe and well tolerated. Conclusion: Ecleralimab significantly attenuated allergen-induced bronchoconstriction and airway inflammation, and was safe in subjects with mild atopic asthma. Ecleralimab significantly attenuated allergen-induced airway responses and inflammation in subjects with mild asthma. It was generally safe and well tolerated, suggesting anti-TSLP may be a promising, new therapeutic class for inhaled asthma treatment. https://bit.ly/3U294EA